Införande av mjuka golv för mjölkkor - Vikström, Simon (2006)
Soft rubber flooring have gained in popularity over the last years. Rubber flooring al-lows cow to move more freely without slipping and improves claw and leg health. The purpose of this study was to investigate the influence of a stepwise introduktion of soft flooring on cow`s placement in cow houses with robotic milking. A case study was carried out in a herd in northern Sweden with 41 cows. Observations were made every 15 minutes between 09.00 and 16.00 concering cow placement in cu-bicles, in cubicle alley, in feeding alley and in feeding alley with the head through feed-ing gate. One observation period was carried out per flooring alternativ: 1) all concrete slatted floor, 2) rubber slatted floor in feeding alley and concrete slatted floor in cubicle alley and 3) rubber slatted floors in feeding alley and solid rubber floors in cubicle alley. The study showed that 6 %-units fewer cows lay in the cubicles when the feeding alley surface was slatted rubber. When all alley floors were rubbered, 16 %-units fewer cows lay in the cubicles compared with when all alleys were concrete slatted floors. The cows spent more time standing and walking, without increasing the time at the feeding table, when soft flooring was available. When the cubicle alley surface was soft instead of hard, 13 %-units more cows used this area. The results implicate that soft flooring enhance natural behaviour of cows. The cows stand or walk more and lie shorter in cubicles. Soft flooring is an excellent option to satisfy dairy cows' demands on welfare and for a thriving prosperous modern milk produc-tion. Mjuka gummimattor som golvunderlag i skrapgångar för mjölkkor har växt i popularitet de sista åren. Gummimattorna har till uppgift att förbättra stallmiljön genom att tillåta kon att förflytta sig halkfritt och komfortabelt, samt att bidra till bättre ben och klövhäl-sa. Mitt syfte med examensarbetet har varit att göra en fallstudie om hur en övergång från hårt till mjukt underlag i skrapgångarna påverkar kons placering i stallet. ...